Creating Innovative Classroom Materials for Teaching Young Children - Debelak, Marianne (Harcourt Brace Jovanovich, Inc, 1981)
Instructions for constructing two hundred classroom materials for young children are presented in this book. It is organized into subject areas that follow most curriculum guides: art, children's literature, health and nutrition, language arts, math, music, physical activities, reading readiness, science, and social studies. Materials in each subject area are accompanied by easy to follow directions, photographs, or detailed line drawings, and strategies for using the materials are included. The introduction includes a discussion of each subject area, advice on how to care for materials, sources for materials, and a bibliography of books and films. (JD)